Legal regime of business partnership property (considering international experience) (Law and Safety, 2023)
The article concludes that property as a special object is a separate thing, a set of things, as well as property rights and obligations. This understanding, despite the existence of certain terminological differences, coincides with its general understanding in the system of legal knowledge of certain countries of the Romano-Germanic legal family, in particular, countries with a pact system of law, and corresponds to the content of Article 1 of Protocol 1 to the Convention for the Protection of Human Rights and Fundamental Freedoms. In the legal literature, it includes any economic benefits, objects of both the material and intangible world, which are in the state of appropriation of a person. At the same time, the word “property”, as used in Article 1 of Protocol 1 to the Convention, refers to an object of economic value. In this sense, property is an economic category and synonymous with the economic concept of “ownership”. This is also indicated by the use of such concepts as “assets”, “funds”, “profit”, “goodwill”, “accumulated intangible assets of the enterprise”, “property of economic value” in the ECHR judgments to describe the category of property.From the legal point of view, it is justified that only things, collections of things, and animals are considered by the legislation and doctrine of the countries of the continental legal system as objects of property rights or other property rights. They are the only ones empowered with a legal regime of things. Such types of benefits as property rights (legal claims) and obligations cannot be owned by a person on the basis of property rights. They may have the legal regime of objects of intellectual property relations, obligations, corporate relations, but not ownership or other property rights.It has been established that property rights are not the only means of securing the assets of business entities. They may also be owned by the latter on the basis of other rights (e.g., obligatory rights). It has been proved that in this case, a business company is not an owner, but, for example, a lessee (tenant), a user under a loan agreement, a mortgage agreement as a mortgagor, etc.
Keywords: business entities; objects of civil rights; property; legal regime of property; things; property rights.